The Influence of Understanding Tax-Accounting towards Compliance Tax Payers Business Entity in the Field of Industry (Empirical Study in North Makassar Tax Office) - Sulfati, Andi (Information Management and Business Review, 2015)
Understanding of tax accounting has contributed greatly to the taxpayer compliance in meeting tax obligations. This study aims to determine the effect of accounting understanding of tax on tax compliance business entities in the field of industry in the North Makassar STO. The approach used in this study is descriptive-quantitative approach. The population in this study is all tax professional company manufacturing middle class listed on STO North Makassar, The sample in this study is the tax professionals who work for companies with criteria (1) have served at least one year, and (2) never fill SPT Agency. The sampling technique in this study using sampling techniques with incidental sampling method. Hypothesis testing using simple regression with the help of statistical software package for the social sciences (SPSS) version 22. Questionnaires were distributed utilizing an ordinal scale through a 5-point Likert Scale. Results from this study indicate that the value of the variable regression coefficient of understanding of accounting tax of 0.722 with t value of 8.832 is greater than the value that is equal to 2.040 t table so it can be stated that the understanding of tax accounting positive and significant (0.02 <0.05), thereby understanding the tax accounting has contributed greatly to the taxpayer compliance in meeting tax obligations. This means that the continuity of work between taxpayers with tax officials.